Controlled Plant Growth in Vertical Farming Systems - Găgeanu, Iuliana; Tăbărașu, Ana-Maria; Gheorghe, Gabriel; Nițu, Mihaela; Pruteanu, Augustina (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The traditional methods of growing crops, such as in greenhouses and open fields, have lately been put to the test by a contemporary invention called vertical farming. According to the amount of the output, the crops are usually stacked shelves and stacked vertically using this method. In order for crops to develop well without any agronomic restrictions, vertical farming integrates a number of technologies, including big data analytics, robotics, the internet of things, artificial intelligence, etc. Structures for vertical farming depend on complete solutions to support the integration of various hardware, data collection, data analysis, and automatic control of the installed devices. Future vertical urban farms will not only boost crop yields or lower production costs, but also vastly enhance the quality of the agricultural goods offered to city inhabitants, minimizing the unfavourable effects of urbanization on the environment. Due to their independence from climatic factors and reduced water requirements, vertical farms can serve the same purposes wherever they are, and locals can gain comparable advantages. The paper presents vertical farm systems as a whole and also a minimum and ideal setting for a vertical farm as a means of increasing food availability and yields, all while ensuring sustainability and environmental protection.